A new species of Volvariella (Pluteaceae, Basidiomycota) from Western Siberia, Russia - Malysheva, Ekaterina; Kapitonov, Vladimir; Malysheva, Vera (Phytotaxa, 2022)
Volvariella clavocystidiata sp. nov., collected from Western Siberia, is described based on morphological characters and molecular data. The new species is characterized by silky fibrillose whitish pileus, clavate cheilo- and pleurocystidia, and basidiospores on average 6.6 × 4.8 µm and swamp habitat. Detailed morphological descriptions, drawings of microstructures and comparisons with closely related taxa are provided. Phylogenetic analyses inferred from the internal transcribed spacer (nrITS) and 28S nuclear ribosomal large subunit (nrLSU) showed that novel taxon formed independent phylogenetic lineage within the genus Volvariella.